Menjaga Budaya melalui Pendidikan: Peran Pendidikan dalam Mencegah Pernikahan Usia Dini - Widhi, Bidari Andaru; Patty, Elyakim Nova Supriyedi; Elthia, Memy Wardani; Alfilail, Nur; Alawiyah, Rosidah (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Early marriage is a classic issue that still becomes the problem in society especially in Lombok. For some society in Lombok, early marriage is common thing that happen. It seems that early marriage may become a tradition. One of area in North Lombok namely Dusun Lokok Beru, Desa Selat, indicates that the number of early marriage is high. From this reality we can infer that this situation is not good for generation in Lombok. Besides that, the parents’ belief that early marriage would carry on the best blessing still stick in parents’ mind without considering the children readiness mentally and financially. Thus, This community service was done in Dusun Lokok Beru, Desa Selat, North Lombok because number of early marriage in this area is quite high. Socialization, presentation, and discussion about accomplishment of 9- year compulsory education are methods that are used to increase the awareness of disadvantages of early marriage in this society.  The result of community service that has been done indicates that there is positive feedback that is gained from the service. It is indicated from the responses of parents in the interview session.